2012
DOI: 10.5539/jms.v2n2p197
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the Environmental Sustainability-Conscious (ESC) Consumer: Proposing the S-P-P Model

Abstract: This paper sought to explore the nature of the various measures used for profiling the environmental sustainability conscious (ESC) consumer segment; and to posit a measure that will be most appropriate for profiling this segment.Design/methodology/approach: Using the 5S model for assessing market segmentation approaches, the study critiqued the common measures, which are singly adopted for profiling the ESC segment.Findings: Contradictory views exist among scholars as to which approach is best for profiling t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Numerous authors have found specific correlations between socio-demographic features and pro-environmental behaviour [13,[16][17][18][19][20][21]. The consumer that has a greater awareness of environmental issues tends to be younger, with a higher level of education, comes from a wealthy family, and has a good employment status.…”
Section: Nationality and Eco-behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors have found specific correlations between socio-demographic features and pro-environmental behaviour [13,[16][17][18][19][20][21]. The consumer that has a greater awareness of environmental issues tends to be younger, with a higher level of education, comes from a wealthy family, and has a good employment status.…”
Section: Nationality and Eco-behaviourmentioning
confidence: 99%
“…Even though pro-environmental behaviour research has developed in different directions [11], including the socio-demographic or psychological determinants of individual ecological behaviour [12,13], we can still consider the impact of nationality as one of the most challenging topics. Even if nationality differences have been included in many studies [14,15], inter-country analysis is not as common in the pro-environmental behaviour literature, especially involving non-American countries.…”
Section: Introductionmentioning
confidence: 99%
“…Tkaczynski and Rundle‐Thiele () used segmentation to segment based on motivations towards attending music festivals, whereas other researchers have segmented consumers based on their demographic information such as gender in wine consumption (Barber, ) and age in proenvironmental behaviours (Van der Kollmuss & Agyeman, ). Demographic approaches often use information such as gender, age, and income as proxies for unobservable variables that can predict behaviour (Mowen & Minor, ; Park & Lee, ; Ukenna, Nkamnebe, Nwaizugbo, Moguluwa, & Olise, ). Yet simply segmenting on demographic variables has received criticism (Dietrich, Rundle‐Thiele, Leo, & Connor, ), as meaningful segments can be identified on the basis of at least four segmentation bases: demographic, psychographic, geographic, and behavioural variables (Kotler, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies (Chan, ; Chekima et al, ; Ukenna et al, ) have investigated the nature of the relationship between ecoliteracy (or environmental knowledge or sustainability literacy) and sustainable consumption. The basic assumption is that knowledge is “recognized in consumer research as a characteristic that influences all phases in the decision process and that knowledge is a significant construct that affects how consumers gather and organize information” (Ukenna et al, , p. 197); this could possibly influence choice and behavior.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…However, it has been pointed out that rather than viewing unsustainability as a concomitant of affluence, it is more logical to see it as resulting from the lifestyles of both the poor and the rich (Nkamnebe, ). Regardless of perspectives regarding source(s) of unsustainable behavior, it appears appropriate to consider unsustainable consumption as a global phenomenon that calls for urgent and coordinated action from the rich and poor consumers as well as developed and developing nations (Ukenna, Nkamnebe, Nwaizugbo, Moguluwa, & Olise, ).…”
Section: Introductionmentioning
confidence: 99%